Rancang Bangun Website Sistem Penjualan Barang Produksi Pada PT Fhadli Usaha Mandiri - Tuti Nurhaeni; Ari Wibowo; Muhamad Rifqi Gian Sabillah (IJAcc, 2022)
PT. Fhadli Usaha Mandiri is a company engaged in the sale of printing shoes, but to market their products they still use the manual method, namely by using the telephone. Sales that are done manually are less effective because of the lack of information from customers about the products being sold. So we need a web-based system that can handle sales so that customers know the products that will be sold by the company and reduce the use of telephones and business cards to provide information to customers about products. The author conducts an analysis using several methods including data collection, system analysis using PIECES and using UML (Unified Modeling Language) as an illustration of the system design to be made and Xampp, PHP and Sublime as text editors. It is hoped that this system can assist customers in finding product information